Electrical circuit model of an aged ceramic humidity sensor. (2019) - Kumar, Shailesh; Kumar, Lokesh; Islam, Tarikul; Kumar Raina, Kuldeep
Abstract: This paper presents the mathematical model and electrical equivalent circuit of an aged parallel plate capacitive sensor fabricated by sol-gel method (γ.-Al2 O3 ). The response of the sensors was simulated using proposed electrical equivalent circuit model and dielectric theory. The electrical equivalent circuit is the parallel combination of the structural and humidity dependent components of the sensors. Simulation of the structural component was done considering structural aging phenomena of the sensor. The response of the developed model has good agreement with the experimental response of the designed sensor. For the experimental response, the designed sensor was kept in open environment for ten months and the experiment was performed to determine the long-time drift and sensitivity which occurs under continuous operation in the range of 3.5 ppm to 101 ppm. The developed model can be used for computation of water stretch in the air pore, level of hydration of the sensing material and drift in the sensor output at any humidity.